2020
DOI: 10.1007/s00705-020-04851-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate

Abstract: Avian infectious bronchitis (IB) is a highly contagious viral respiratory disease, caused by infectious bronchitis virus (IBV), that poses an important economic threat to the poultry industry. In recent years, genotypes GI-7, GI-13, and GI-19 have been the most prevalent IBV strains in China. However, in this study, we found that most IBV strains from southern China in 2016-2017 belonged to genotype GVI-1. This genotype, for which there is no vaccine, has been reported sporadically in the region. The GDTS13 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The GI-1 and GI-12 lineages representing the old Massachusetts (Mass) and 793B lineages, respectively, have been found in all IB-endemic countries, while other lineages are found only in specific parts of the world. The 4/91-like and QX-like IBV strains belong to lineage GI-13 and GI-19, respectively, whereas the Israeli variant II and Egyptian variants I and II belong to the GI-23 lineage [ 14 , 37 ]. IBV variants of the GI-23 lineage circulate in the Middle East and continue to spread in many countries in Africa, Asia, and Europe [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GI-1 and GI-12 lineages representing the old Massachusetts (Mass) and 793B lineages, respectively, have been found in all IB-endemic countries, while other lineages are found only in specific parts of the world. The 4/91-like and QX-like IBV strains belong to lineage GI-13 and GI-19, respectively, whereas the Israeli variant II and Egyptian variants I and II belong to the GI-23 lineage [ 14 , 37 ]. IBV variants of the GI-23 lineage circulate in the Middle East and continue to spread in many countries in Africa, Asia, and Europe [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current epidemic H9N2 AIV (A/chicken/ Hunan/HN/2015) belonged to the h9.4.2.5 lineage, as described previously ( 34 ). The IBV belonged to the QX-like genotype, TJ401, as described previously ( 35 ). Both viruses were propagated in 10-day-old SPF chicken embryos and stored at −80°C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The IBV belonged to the QX-like genotype, TJ401, as described previously (35). Both viruses were propagated in 10-day-old SPF chicken embryos and stored at −80 • C for further analysis.…”
Section: Viruses and Animalsmentioning
confidence: 99%
“…89,90 IBV is a contagious avian coronavirus that can infect respiratory tract of chicken and in poultry industry is a major problem. 91 Zhang et al 92 showed that chicken MBL by the interaction to S1 spike protein of IBV plays a role in innate and the adaptive immune response. In avian bone marrow-derived dendritic cells (BMDCs) infected with IBV, levels of two lncRNAs MANBAL and POMT2 were downregulated.…”
Section: Avian Infectious Bronchitis Virus (Ibv)mentioning
confidence: 99%